DNA vaccination via RALA nanoparticles in a microneedle delivery system induces a potent immune response against the endogenous prostate cancer stem cell antigen. (15th September 2019) - Cole, Grace; Ali, Ahlam A.; McErlean, Emma; Mulholland, Eoghan J.; Short, Amy; McCrudden, Cian M.; McCaffrey, Joanne; Robson, Tracy; Kett, Vicky L.; Coulter, Jonathan A.; Dunne, Nicholas J.; Donnelly, Ryan F.; et al.
Graphical abstract: Abstract: Castrate resistant prostate cancer (CRPC) remains a major challenge for healthcare professionals. Immunotherapeutic approaches, including DNA vaccination, hold the potential to harness the host's own immune system to mount a cell-mediated, anti-tumour response, capable of clearing disseminated tumour deposits. These anti-cancer vaccines represent a promising strategy for patients with advanced disease, however, to date DNA vaccines have demonstrated limited efficacy in clinical trials, owing to the lack of a suitable DNA delivery system. This study was designed to evaluate the efficacy of a two-tier delivery system incorporating cationic RALA/pDNA nanoparticles (NPs) into a dissolvable microneedle (MN) patch for the purposes of DNA vaccination against prostate cancer. Application of NP-loaded MN patches successfully resulted in endogenous production of the encoded Prostate Stem Cell Antigen (PSCA). Furthermore, immunisation with RALA/pPSCA loaded MNs elicited a tumour-specific immune response against TRAMP-C1 tumours ex vivo . Finally, vaccination with RALA/pPSCA loaded MNs demonstrated anti-tumour activity in both prophylactic and therapeutic prostate cancer models in vivo . This is further evidence that this two-tier MN delivery system is a robust platform for prostate cancer DNA vaccination. Statement of Significance: This research describes the development and utilisation of our unique microneedle (MN) DNA delivery system, which enables penetration through the stratum corneum and deposition of the DNA within the highly immunogenic skin layers via a dissolvable MN matrix, and facilitates cellular uptake via complexation of pDNA cargo into nanoparticles (NPs) with the RALA delivery peptide. We report for the first time on using the NP-MN platform to immunise mice with encoded Prostate Stem Cell Antigen (mPSCA) for prostate cancer DNA vaccination. Application of the NP-MN system resulted in local mPSCA expression in vivo. Furthermore, immunisation with the NP-MN system induced a tumour-specific cellular immune response, and inhibited the growth of TRAMP-C1 prostate tumours in both prophylactic and therapeutic challenge models in vivo.